Metabolomic Responses of Maize Shoots and Roots Elicited by Combinatorial Seed Treatments With Microbial and Non-microbial Biostimulants - Rouphael, Youssef; Lucini, Luigi; Miras-Moreno, Begoña; Colla, Giuseppe; Bonini, Paolo; Cardarelli, Mariateresa (Frontiers in Microbiology, 2020)
Microbial and non-microbial plant biostimulants have been successfully used to improve agriculture productivity in a more sustainable manner. Since the mode of action of biostimulants is still largely unknown, the present work aimed at elucidating the morpho-physiological and metabolomic changes occurring in maize (Zea mays L.) leaves and roots following seeds treatment with i) a consortium of two beneficial fungi (arbuscular mycorrhizal fungi – AMF, and Trichoderma koningii TK7) and rhizobacteria, ii) protein hydrolysate-based biostimulant (PH) alone or iii) in combination with a consortium of T. koningii TK7 and rhizobacteria. The application of PH alone or in combination with Trichoderma elicited significant increases (+16.6%) in the shoot biomass compared to untreated maize plants, whereas inoculation with AMF + Trichoderma elicited significant increases of root dry biomass (+48.0%) compared to untreated plants. Distinctive metabolomic signatures achieved from the different treatments, hence suggesting that different molecular processes were involved in plant response to biostimulants. The metabolic reprogramming triggered by the treatments including the protein hydrolysate was hierarchically more pronounced than the application of microorganisms alone. The most of differential metabolites could be ascribed to secondary metabolism, with phenylpropanoids and terpenes being the most represented compounds. The application of the PH triggered an accumulation of secondary metabolites, whereas the direction of regulation was opposite in the case of microorganisms alone. Notwithstanding, the increase in biomass could be related to two processes, namely the modulation of the multilayer phytohormones interaction network and a possible increase in nitrogen use efficiency via the GS-GOGAT system.